Prenatal Opioid Maintenance in the United States and Its Effect on Neonatal Abstinence Syndrome: The Case of West Virginia's Opioid Epidemic. Issue 3 (July 2019) - Ruley, Morgan; Coustasse, Alberto
Abstract : West Virginia's opioid epidemic has been the cause of more than 42 000 deaths each year. Opioid abuse has become an issue among pregnant mothers and has increased the effects of neonatal abstinence syndrome (NAS) in infants. The purpose of this study was to evaluate the participation of prenatal opioid maintenance to determine whether it has decreased the amount of treatment needed for NAS in infants in West Virginia. The methodology utilized a literature review complemented with a semistructured interview. Thirty-six sources were referenced for this literature review. It was found that buprenorphine maintenance therapy had the most positive effect on NAS after birth. This review also reported a lack of availability for addicted pregnant women to enroll in maintenance programs and a high dropout rate. Opioid maintenance therapy has permitted pregnant women to refrain from illicit drug use without experiencing withdrawal symptoms, and it has allowed the opportunity for their infants to have better health after birth.